Risk factors observed in the last 30 days of life among student suicides: distinguishing characteristics of college and university student suicides. Issue 5 (22nd June 2022) - Berman, Alan L.
Abstract: Purpose: Studies of college and university student suicide have identified predictors only of suicide ideation and attempts and have relied solely on self-report data. This study explores risk factors observed in the last 30 days of life of college and university students who died by suicide, compared to those of high school and middle school students. Methods: Retrospective chart reviews of 16 college and university students (aged 19–26) were abstracted and compared to those of 24 middle and high school students (aged 12–18), all in, or recently in, clinical care. Results: Near-term risk factors for deaths by suicide largely were equivalent in compared groups, with only sleep problems, conduct problems, and passive suicide ideation found to be significantly different between student cohorts. Conclusions: These preliminary findings are hypotheses-generating for larger studies of more restricted age ranged youth cohorts needed to better differentiate near-term risk factors for suicide.